Long-term survival following lung surgery for cancer in high-risk patients after perioperative pulmonary rehabilitation. (28th July 2018) - Marhic, Alix; Dakhil, Bassel; Plantefeve, Gaëtan; Zaimi, Rym; Oltean, Viorel; Bagan, Patrick
Abstract: OBJECTIVES: The benefits of a rehabilitation programme before lung surgical resection for cancer remain to be defined. The purpose of this observational study was to assess the efficacy of preoperative rehabilitation and postoperative rehabilitation on short- and long-term outcomes in patients who were at high operative risk. METHODS: Between January 2010 and December 2012, 20 consecutive non-operable patients (16 men and 4 women, mean age 66 years) with clinical N0 lung cancer were included. Eligibility criteria were lung function below guideline thresholds and/or associated severe comorbidities. The protocol included a cardiorespiratory perioperative rehabilitation programme. These patients were followed up at 5 years. RESULTS: The average increase in forced expiratory volume (FEV)1 and of VO2max preoperatively was 12% and 3.5 ml/kg/min, respectively. All patients underwent a pulmonary surgical resection procedure. The morbidity and mortality rates were 20% and 5%, respectively. Nineteen patients returned home upon the completion of postoperative rehabilitation. After 5-year follow-up, the Kaplan–Meier 5-year survival rate was 52%. CONCLUSIONS: Perioperative pulmonary rehabilitation seems to allow surgical management of lung cancer by lung resection in first-line, non-eligible patients. The long-term survival of operated high-risk patients is encouraging despite the high complication rate.